The effects of Zn/Fe co-dopants on the structural, thermal, magnetic, and in vitro biocompatibility properties of calcium pyrophosphate ceramics - Kebiroglu, Hanifi; Ates, Tankut; Bulut, Niyazi; Ercan, Ismail; Ercan, Filiz; Acari, Idil Karaca; Kaygili, Omer (Elsevier, 2022)
In the present work, calcium pyrophosphate (CPP) samples co-doped with Zn and Fe were prepared by using a wet chemical method, and their thermal, magnetic, structural, morphologic, and in vitro biocompatibility properties were investigated for the first time. X-ray diffraction (XRD) results showed that a continuous decreasing trend in two lattice parameters, unit cell volume, and average crystallite size was observed with the increasing Zn content. Zn content affected the magnetic and thermal behaviors, cell viability property of the CPP, as well as morphology. The sample containing 0.22 at.% Zn and 0.22 at.% Fe showed the best biocompatibility among all the samples, and the higher amount of Zn caused the lower cell viability. The bandgap of the CPP decreased with adding of Zn, while the linear absorption coefficient value increased.
Keywords: Ceramics; Calcium pyrophosphate; X-ray diffraction (XRD); Cell viability